UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN LABU KUNING (Cucurbita moschata Duchesne.) TERHADAP BAKTERI Staphylococcus aureus - Sihotang, Febri Yanti (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Pumpkin leaves (Cucurbita moschata Duchesne.) is a food ingredient that is often used as a complementary food for breast milk such as porridge and various other processed foods. Pumpkin is known to contain flavonoids, tannins and saponins. This study aimed to test the antibacterial activity of pumpkin leaf extract (Cucurbita moschata Duchesne.) against bacteria and Staphylococcus aureus. Antibacterial activity was tested by disc diffusion method. The ethanol extract of pumpkin leaves was made using the cold method, namely maceration using 70% ethanol, then obtained a thick extract using a rotary evaporator and a water bath. The results of the examination were 4.60% water content, 19.11% water soluble extract, 23.42% ethanol soluble extract, 5.87% total ash content, 0.68% acid insoluble ash content. The results of this study showed the antibacterial activity of ethanol extract of pumpkin leaves at various concentrations of 10% (21.56 mm), 20% (22 mm), 30% (22.56 mm), 40% (22.56 mm) DMSO 10% as a negative control (-) and chloramphenicol as a positive control (40.66 mm). So it can be concluded that the ethanol extract of pumpkin leaves has good antibacterial activity against Staphylococcus aureus bacteria.